Synthetic compounds from an in house library as inhibitors of falcipain-2 from Plasmodium falciparum - Bertoldo, Jean Borges (2015)
Falcipain-2 (FP-2) is a key cysteine protease from the malaria parasite Plasmodium falciparum. Many previous studies have identified FP-2 inhibitors; however, none has yet met the criteria for an antimalarial drug candidate. In this work, we assayed an in-house library of non-peptidic organic compounds, including (E)-chalcones, (E)-N'-benzylidene-benzohydrazides and alkyl-esters of gallic acid, and assessed the activity toward FP-2 and their mechanisms of inhibition. The (E)-chalcones 48, 54 and 66 showed the lowest IC50 values (8.5±0.8μM, 9.5±0.2μM and 4.9±1.3μM, respectively). The best inhibitor (compound 66) demonstrated non-competitive inhibition, and using mass spectrometry and fluorescence spectroscopy assays, we suggest a potential allosteric site for the interaction of this compound, located between the catalytic site and the hemoglobin binding arm in FP-2. We combined structural biology tools and mass spectrometry to characterize the inhibition mechanisms of novel compounds targeting FP-2.